Analysis of onset time and intubating conditions following intravenous administration of Rocuronium 0.6mg/kg and Rocuronium 0.9mg/kg doses and its comparison with Succinylcholine 1.5mg/kg for Rapid Sequence Induction (Pain medicine, 2023)
Background: The purpose of this study was to compare rocuronium to succinylcholine in adult patients undergoing elective surgery using two different doses of 0.6 mg/kg and 0.9 mg/kg for rapid sequence endotracheal intubation.Methodology: Total of 90 cases were randomly divided into three groups of 30 in each. Group S was intubated with 1.5 mg/kg body weight succinylcholine chloride, group R1 intubated with 0.6 mg/kg body weight rocuronium bromide, and group R2 was intubated with 0.9 mg/kg body weight rocuronium bromide.Results: 90% in group S, 53.33% in group R1, and 76.67% in group R2 cases had excellent intubating conditions. The onset time of group S was significantly shorter than that of group R2 and group R1 doses. There was statistical significance difference observed among group S, group R1, and group R2 regarding clinical onset of action (45.58±4.198, 56.38±5.032, and 52.59±3.966 seconds).  Group S, group R1, and group R2 had mean duration of action of 5.24±1.453, 23.96±2.14, and 43.18±2.12 minutes respectively. In group R1 and group R2, the mean heart rates were increased by 47.1% and 33.9%, and mean arterial pressure increased by 28.56% and 24.92% observed one min after intubation, and returned to preinduction levels after 5 minutes. In all three groups, no significant side effects were observed.Conclusion: Rocuronium at 0.9 mg/kg dose is preferable and alternative to succinylcholine in cases where succinylcholine is contraindicated
Keywords: rapid sequence induction; succinylcholine chloride; rocuronium bromide; intubation